Modelo de captación de talento humano en la Unidad Educativa “Jean Piaget”. - Calvache Jiménez, Jhoselyn Dayana (2023)
Organizations worldwide have a high turnover rate due to inadequate recruitment of personnel. Moreover, this problem is evident not only in large companies, but also in small institutions, as is the case of the “Jean Piaget” Educational Unit. There are problems in the recruitment processes for not carrying out the sub-processes in a structured and documented manner; in addition, a turnover rate of about 19% is evidenced as a possible cause of the incorrect recruitment of personnel; therefore, the objective is to propose a model of personnel recruitment, applying a qualitative-quantitative approach. The descriptive method was also used for the improvement of the recruitment, selection, hiring and induction subprocesses, then a cross-sectional analysis was performed. Two instruments were used: 1 survey with 18 questions applied to 32 employees, 1 interview with the administrator responsible for human talent management. The most important results of the research show that 84% of the collaborators did not receive a formally written invitation in their recruitment, most of them are part of the institution through personal references. Additionally, 38% mentioned that there were omissions in the selection sub-process; all employees consider that an induction sub-process is important and the administrator emphasizes the lack of pre-established conditions for hiring. The proposal seeks to improve the planning and recruitment process; it is recommended to establish an annual budget that allows to efficiently carry out the recruitment process and thus optimize the use of resources.